ChemInform Abstract: Regiospecific Synthesis of 1‐Trifluoromethylisoquinolines Enabled by Photoredox Somophilic Vinyl Isocyanide Insertion. Issue 11 (March 2015) - Cheng, Yuanzheng; Yuan, Xiangai; Jiang, Heng; Wang, Ruzhi; Ma, Jing; Zhang, Yan; Yu, Shouyun
Abstract The title reaction is achieved from isocyanides of type (I), (IV), and (VII) with Umemoto′s reagent (II) in the presence of an Ir‐catalyst.